2019
DOI: 10.1002/pmrj.12240
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Event Profiles of High Dose Botulinum Toxin Injections for Spasticity

Abstract: Background Botulinum toxin injections are effective in relieving focal spasticity resulting from upper motor neuron injuries. Doses approved in the United States for onabotulinumtoxinA and incobotulinumtoxinA are up to 400 units, yet higher doses are often used. Objective To determine differences in risk of adverse events when using higher (>600 units) as compared to lower doses within clinically applicable categories; the difference in adverse events between types of botulinum toxin‐A, and any association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…In this study, 155 subjects were enrolled, but only 11 (7.1%) suffered from traumatic brain injury [38]. The remaining two investigations did not report the number of spastic subjects according to aetiology [39] or spasticity aetiology [29]. Since these studies had mixed samples, the investigation by Ianieri et al was described in the stroke paragraph and that by Kirshblum et al was reported in the paragraph concerning studies with mixed samples.…”
Section: Brain Injurymentioning
confidence: 97%
See 4 more Smart Citations
“…In this study, 155 subjects were enrolled, but only 11 (7.1%) suffered from traumatic brain injury [38]. The remaining two investigations did not report the number of spastic subjects according to aetiology [39] or spasticity aetiology [29]. Since these studies had mixed samples, the investigation by Ianieri et al was described in the stroke paragraph and that by Kirshblum et al was reported in the paragraph concerning studies with mixed samples.…”
Section: Brain Injurymentioning
confidence: 97%
“…Of studies that enrolled mixed samples, mild AEs consisting of generalised weakness (12%), feeling of residual urine (10%), constipation (9%) and blurred vision (8%) were observed by Dressler et al, but these disturbances were attributed to underlying neurological conditions and not to the effect of BTX-A [11]. The study by Kirshblum et al analysed if adverse events increased when injecting higher doses of BTX-A, and if onaBTX-A or incoBTX-A differed in adverse event rates [29]. They reported that AEs did not increase until doses of BTX-A exceeded 600 U. AEs were observed in 7 subjects (5.6%), 4 (2.2%) and 16 (2.6%) treated by ≤400U; 400-600 U and >600 U of BTX-A, respectively.…”
Section: Safety and Adverse Eventsmentioning
confidence: 99%
See 3 more Smart Citations